Chemically treated microwave-derived biochar: An overview - Rafeah, Wahi; Nur Fakhirah Qurratu'ain, Zuhaidi; Yusralina, Yusof; Jamliah, J; Kanakaraju, Devagi; Zainab, Ngaini (Elsevier Ltd., 2017)
Biochar, a carbon-rich material, can be produced via microwave pyrolysis, as a more energy and cost saving method compared to conventional externally heated pyrolysis. Biochar has versatile applications, for example, for soil amendment purpose and pollutant removal from wastewater. Chemical treatment has been proven to improve the physical and chemical properties of biochar for better applicability. Thus, extensive amount of research has been conducted on chemical treatment of conventional biochar, and several review articles have discussed published works on the chemically treated conventional biochar. However, there has been no review on works involving the chemically treated microwave-derived biochar, by far. This paper presents an overview of the current development and improvement on chemical treatment methods and applications of microwave-derived biochar.